ANALISIS KINERJA KARYAWAN PT. AGROBISNIS PANCA EKATAMA - Estiana, Ria; Karomah, Nurul Giswi; Budiasningrum, Retno Setya; Khoerunisa, Eva (Universitas YPPI Rembang, 2022)
Performance is the result of a process of completing work and the behavior needed to achieve the desired results. An embodiment of work performed by employees and is generally used as a basis or reference for evaluating employees in an organization. Efforts to improve employee performance, companies can choose several ways that are in accordance with the company's capabilities, including by providing compensation. In addition to compensation, factors that affect employee performance are work motivation. Motivation is the giving of individual impulses to act that causes the person to behave in a certain way that leads to goals. Psychologically, the enthusiasm and enthusiasm of an employee in carrying out his work is strongly influenced by work motivation. The motivation that exists in employees is expected by individuals to work hard and be disciplined in their work. The purpose of this study was to determine the effect of compensation and work motivation together (simultaneously) or (partial) on the performance of employees of PT. Panca Ekatama Agribusiness. The type of research conducted is descriptive quantitative research. The sample in this study were 66 respondents. The technique used is a random sampling technique, probability sampling. The data analysis method used is descriptive analysis and multiple linear regression analysis. The results of the descriptive analysis show that compensation is included in the very high category, work motivation is included in the high category, and employee performance is included in the very high category. The partial test shows that compensation has no positive and insignificant effect on employee performance and work motivation has a positive and significant effect on employee performance. And the results of the simultaneous test show that compensation and work motivation together have a positive and significant effect on employee performance. In this study, the coefficient of determination for Employee Performance was 0.477. This means that variations in employee performance can be explained by 47.7% by variations in compensation and work motivation. The remaining percentage of 52.3% indicates that there is still influence from factors or variables that are not included in this study. Among the factors that influence employee performance is the amount of compensation that can affect employee performance.Keywords: compensation, work motivation and employee performance.